(untitled) - Holesa, Lukas (Doprava a spoje, 2012)
The contribution strives to reflect the significance of individual testing procedures for the protection of a pedestrian, such as various reality simulations. Also with regard to the fact that the risk of accidents cannot be fully prevented, the contribution tries to aim at and analyse also the area of passive safety. It points to the justification and importance of especially external measures on a vehicle, such as integrated concept connecting active engine bonnet with extended system of a blow-up bag for the protection of pedestrians. The contribution further describes new principles and technologies, with which these testing procedures and safety systems work and subsequently individual advantages and merits thereof are mentioned